2006
DOI: 10.1165/rcmb.2005-0398oc
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of CYP51 from Mycobacterium avium

Abstract: Mycobacterium avium complex (MAC) causes chronic lung disease in immunocompetent people and disseminated infection in patients with AIDS. MAC is intrinsically resistant to many conventional antimycobacterial agents, it develops drug resistance rapidly to macrolide antibiotics, and patients with MAC infection experience frequent relapses or the inability to completely eradicate the infection with current treatment. Treatment regimens are prolonged and complicated by drug toxicity or intolerances. We sought to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…At the dawn of the new millennium, the orthologous nature of the first prokaryotic CYP51-like gene in Mtb was confirmed phylogenetically [61] and biochemically [62, 63]. CYP51 is not unique to Mtb since it is conserved in the mycobacterium genus [64, 65] and other actinomycetes-related species (Table S1, supporting material). An ortholog was also found and characterized in an obligate methanotrophic gram-negative bacterium Methylococcus capsulatus [66].…”
Section: Structural and Biochemical Analysis Of Individual Enzymesmentioning
confidence: 99%
“…At the dawn of the new millennium, the orthologous nature of the first prokaryotic CYP51-like gene in Mtb was confirmed phylogenetically [61] and biochemically [62, 63]. CYP51 is not unique to Mtb since it is conserved in the mycobacterium genus [64, 65] and other actinomycetes-related species (Table S1, supporting material). An ortholog was also found and characterized in an obligate methanotrophic gram-negative bacterium Methylococcus capsulatus [66].…”
Section: Structural and Biochemical Analysis Of Individual Enzymesmentioning
confidence: 99%
“…Multiple in vitro approaches have suggested that a transmembrane anchor is not always required for the catalytic activity of some microsomal preparations of cytochrome P450s (29,30). For example, M. tuberculosis CYP51 specifically converts detergent-solubilized lanosterol to its demethylated product (31). However, the in vivo role of the membrane anchor in catalysis by other CYP51s that use membrane-associated lanosterol has yet to be established.…”
Section: Significancementioning
confidence: 99%
“…M. smegmatis CYP51 bound clotrimazole, econazole, and miconazole with a two-to threefold-higher affinity than CYP164A2 (Table 2), in contrast to itraconazole, ketoconazole, and voriconazole, for which CYP164A2 and CYP51 had similar affinities. CYP164A2-binding affinities for clotrimazole, (30).…”
Section: Figmentioning
confidence: 99%